(untitled) (Journal of Fiber Bioengineering and Informatics, 2021)
The jersey knitwear market occupies most of the knitting market due to its relatively simple manufacturing process and high public acceptance. Pattern design composed of some simple lines and geometric patterns usually applied to jersey knitwear, but it can not take advantage of knitting fabrics as much as possible. Therefore, in order to combine the merit of knitwear, the research process is as follows: firstly, learning about women's preferences for knitwear in their 30s and 50s through questionnaire distribution and in-store inquiries. Secondly, designing and producing urban women's knitwear collections with optical illusion patterns. The yarn used in this design experiment is mostly 100% 80s Australian wool, and the equipment is STOLL M1 plus–a computerized at knitting machine, all of which are provided and assisted by the FSF factory, Suzhou, China. It is determined that the jacquard pattern put into production is double-sided birdeye jacquard and air layer jacquard. In terms of the collection effect, the design ideas of F̈ake Two Piecesänd S̈imulated Pleated Skirtäre reflected in the collection named c̈hengSHi\". The combination of knitwear and optical illusion patterns dramatically simplithe production process and improves production efficiency owing to knitwear's one-piece weaving. Moreover, it also provides new inspiration for knitwear design.